Institutionalized elderly: vulnerabilities and strategies to cope with Covid-19 in Brazil - Pricila Oliveira de Araújo; Maria Yaná Guimarães Silva Freitas; Evanilda Souza de Santana Carvalho; Thaís Moreira Peixoto; Maria Lúcia Silva Servo; Laiane da Silva Santana; Juliana Macêdo dos Santos Silva; Jenny Caroline Vieira Moura (Universidad de Antioquia, 2021)
This article presents a systematized reflection and discussion around two guiding axes: the first discusses aging and vulnerabilities to biological, physical, cognitive, social and affective losses that require specific attention, as well as vulnerabilities to COVID-19 to which institutionalized elderly people are exposed; the second, we reflect on the adoption of restrictive and protective measures to prevent the spread of the virus, aiming to keep the elder health and mitigate the effects of the pandemic. The conclusion is that the pandemic has increased the many vulnerabilities to which institutionalized older people were already exposed, adding vulnerability to a new disease, such as COVID-19, due to its high lethality and comorbidity, aggravated by precariousness of long-term Brazilian institutions due to the negligence of public authorities, civil society, the management of the institution and the families of the patients. The post-pandemic scenario will require collective efforts to protect and ensure the survival of the elderly living in those residences.